Treatment in Schizophrenia: factors for adherence - Francisca Caiado de Bragança (2020)
This narrative review analyzes the existing scientific evidence on factors related to medication adherence in schizophrenia. Using PubMed as the database, a research was conducted targeting articles published between 2009 and 2019, written in English or Portuguese, about predictors of antipsychotic compliance in schizophrenia. Factors affecting adherence have been generally subdivided into 4 categories: disease-related, patient-related, medication-related and environmental-related. Factors which were found to be consistently associated with poor adherence include poverty, high symptom burden, high levels of hostility, poor insight, presence of substance abuse, negative attitudes toward medication and antipsychotic side-effects. On the other hand, variables such as neurocognitive dysfunction, type of antipsychotic, social support and demographic parameters often yielded contradictory results. Variables consistently associated with non-adherence should be assessed in clinical practice and strategies put in place to correct them or dampen their effect. Since conflicting results are often found regarding several studied variables, future research should aim at identifying further predictors of adherence in order to better guide clinicians and maximize the patient's benefit of treatment.